Аnalysis and control of accounts payable at small business - M. N. Smagina; M. V. Kryukova; V. A. Komarova (Путеводитель предпринимателя, 2021)
Large companies can afford to maintain a staff of financial analysts who study financial indicators using the most modern estimation and predictive methods. Small businesses usually experience financial difficulties and do not have such opportunities. For him, in connection with the above, there is an urgent need to develop reasonable and fairly simple methods for evaluating the results of managerial and economic activities. Analytical research of the existing accounts payable and its ratio to the accounts receivable allows us to assess the real state of finances. The study of the company’s obligations, and primarily accounts payable, is of particular importance for the purpose of management. The optimal one is not the complete absence of debts from a market entity, but the presence of an optimal amount of accounts payable. The main indicator is the timeliness of its repayment. In this case, borrowed funds contribute to the development of production. Overdue accounts payable generates illiquidity, the insolvency of a market entity.